Advice to Rest for More Than 2 Days After Mild Traumatic Brain Injury Is Associated With Delayed Return to Productivity: A Case-Control Study - Silverberg, Noah D.; Otamendi, Thalia (Frontiers in Neurology, 2019)
Objectives: Recent expert agreement statements and practice guidelines for mild traumatic brain injury (mTBI) management no longer support advising patients to “rest until asymptomatic,” and instead recommend gradual return to activity after 1-2 days of rest. The present study aimed to: (i) document the current state of de-implementation of prolonged rest advice, (ii) identify patient characteristics associated with receiving this advice, and (iii) examine the relationship between exposure to this advice and clinical outcomes. Methods: In a case-control design, participants were prospectively recruited from two concussion clinics. They completed self-report measures at clinic intake (Rivermead Postconcussion Symptom Questionnaire, Personal Health Questionnaire-9, and Generalized Anxiety Disorder-7) as well as a questionnaire with patient, injury, and recovery characteristics and the question: “Were you advised by at least one health professional to rest for more than 2 days after your injury?” Results: Of the eligible participants (N=146), 82.9% reported being advised to rest for more than 2 days (exposure group). This advice was not associated with patient characteristics, including gender (95% CI odds ratio = 0.48–2.91), race (0.87–6.28) age (0.93–1.01), a history of prior mTBI(s) (0.21–1.20) or psychiatric problems (0.40– 2.30), loss of consciousness (0.23–2.10), or access to financial compensation (0.50–2.92). In generalized linear modeling, exposure to prolonged rest advice predicted return to productivity status at intake (B= -1.06, chi-squared(1)=5.28, p=0.02; 64.5% in the exposure group vs. 40.0% in the control were on leave from work/school at the time of clinic intake, 19.8% vs. 24% had partially returned, and 11.6% vs. 24% had fully returned to work/school). The exposure group had marginally (non-significantly) higher post-concussion, depression, and anxiety symptoms. Conclusions: mTBI patients continue to be told to rest for longer than expert recommendations and practice guidelines. This study supports growing evidence that prolonged rest after mTBI is generally unhelpful, as patients in the exposure group were less likely to have resumed work/school at 1-2 months post-injury. We could not identify patient characteristics associated with getting prolonged rest advice. Further exploration of who gets told to rest and who delivers the advice could inform strategic de-implementation of this clinical practice.